Shear bond strength ‎of three different ‎bonding agents on ‎three different tooth ‎substrates in ‎different times - Mustafa, Ammar A.; Ibrahim, Maan; Junaidi, termizi; Akhtaruzzaman, Md. (2009)
Introduction:‎